Effects of effective microorganisms (EMs) on growth of red tilapia (Oreochromis sp.) - Muhamad Shahril Zaini.
An experiment was conducted to investigate the effect of different application of EM-1 as a commercial probiotics in feed and water on growth performance of red tilapia (Oreochromis sp.). This experiment was conducted at Hatchery Complex of the Department of Aquaculture, Faculty of Agriculture of UPM Serdang, Selangor. The experiment lasted for 8 weeks from June 2009 until July 2009. Three treatments were applied in this study to understand better the effect of commercial probiotics products which is the Treatment 1 (T1) used as the control in this study, while Treatment 2 (T2) used EMs as an addition in the feed. For Treatment 3 (T3) the EMs used as an addition into the water with ratio 1 : 5000. Each treatment was replicated three times. The experiment was applied in 9 aquaria each was stocked randomly with 30 red tilapia fingerlings (Oreochromis sp.) with an average initial body weight 2.79g. Generally, growth performance feed conversion ratio and survival rate were improved for red tilapia in treatment with edition of EM-1 as a probiotic compared to the control. In term of weight measurements, significant differences (P≤0.05) were recorded among the treatments, while in term of length measurement, no significantly difference (P≥0.05) were recorded among the treatment. For the percentage of survival rate have significant difference (P≤0.05) among the treatments. These results revealed that using EM-1 as a probiotic was the best in terms of growth performance.